2019
DOI: 10.4025/actascibiolsci.v41i1.47323
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in a population of <i>Astyanax scabripinnis<i>: recent bottleneck and the possible influence of individuals with B chromosomes

Abstract: Access the genetic variability of endangered and isolated populations has become an important conservation tool. Astyanax scabripinnis is a well-known fish model for genetic studies, forming very isolated populations in headwaters. Besides that, this species frequently presents supernumerary chromosomes, which elevates the interest on genetic studies. Genetic diversity of an Astyanax scabripinnis population from the Atlantic Forest (Serra da Mantiqueira region, Brazil) was assessed with microsatellite markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The total DNA was extracted using the CTAB method (Cetyltrimethylammonium bromide) (Boyce et al, 1989). We selected six polymorphic microsatellite loci (Table S1) described by Zaganini et al (2012) to Psalidodon (~Astyanax) altiparanae (Characiformes), whose transferability has already been tested to P. scabripinnis (Limeira et al, 2019). The amplifications were made using the GoTaq™ Green Master Mix Kit from Promega, with forward primers plus M13 tail and with the universal primer M13 (Schuelke, 2000) marked with FAM, HEX, and NED.…”
Section: Microsatellitesmentioning
confidence: 99%
“…The total DNA was extracted using the CTAB method (Cetyltrimethylammonium bromide) (Boyce et al, 1989). We selected six polymorphic microsatellite loci (Table S1) described by Zaganini et al (2012) to Psalidodon (~Astyanax) altiparanae (Characiformes), whose transferability has already been tested to P. scabripinnis (Limeira et al, 2019). The amplifications were made using the GoTaq™ Green Master Mix Kit from Promega, with forward primers plus M13 tail and with the universal primer M13 (Schuelke, 2000) marked with FAM, HEX, and NED.…”
Section: Microsatellitesmentioning
confidence: 99%
“…Limeira et al [ 90 ] showed that individuals with B chromosomes are genetically differentiated from 0B individuals in the population of the Lavrinha stream: 0B individuals have private alleles and the B-harboring subpopulation have monomorphic locus and heterozygosity excess. They also demonstrated a recent bottleneck largely driven by the B-harboring subpopulation.…”
Section: B Chromosome and Speciationmentioning
confidence: 99%